Introduction to handling danger signs of pregnancy in pregnant women in an effort to reduce maternal mortality cases at the Plamboyan IV Posyandu - Suhartini, Suhartini; Ani, Ani; Ghita, Dwi; Eppang, Yudiarsi (Journal of Evidence-Based Community Health, 2024)
Prevention of maternal mortality is one of the most important goals of maternal and neonatal services. The Maternal Mortality Rate (MMR) is one of the important indicators of public health. The causes are bleeding, hypertension in pregnancy, infection, abortion and prolonged labor. The results of the activity show that mothers and families are active in participating in counseling and the results of health examinations still find pregnant women in the high-risk category. Until now, the maternal mortality rate (MMR nashi is around 305 per 100,000 live births, the target of 183 per 100,000 live births in 2023 has not been achieved. Likewise, babies and toddlers still have to be saved from death.